Practice of the use of drones in implementation of construction projects in ukraine - Zeltser, R.; Kolot, M.; Panasiuk, I. (Ways to Improve Construction Efficiency, 2018)
The article presents data on the experience of using drones and special software on construction projects in Ukraine. A brief description of the problems encountered by companies performing construction work and ways to solve them using drones is given. The conclusion is that drone is a promising tool that has a wide scope of application at all stages of the implementation of construction projects.